Communication principles and practices for making shared decisions about renal replacement therapy: a review of the literature. Issue 5 (September 2021) - Saeed, Fahad; Shah, Amna Yousaf; Allen, Rebecca Jane; Epstein, Ronald M.; Fiscella, Kevin A.
Abstract : Purpose of review: To provide an overview of the skill set required for communication and person-centered decision making for renal replacement therapy (RRT) choices, especially conservative kidney management (CKM). Recent findings: Research on communication and decision-making skills for shared RRT decision making is still in infancy. We adapt literature from other fields such as primary care and oncology for effective RRT decision making. Summary: We review seven key skills: (1) Announcing the need for decision making (2) Agenda Setting (3) Educating patients about RRT options (4) Discussing prognoses (5) Eliciting patient preferences (6) Responding to emotions and showing empathy, and (7) Investing in the end. We also provide example sentences to frame the conversations around RRT choices including CKM.